(untitled) (AmeriQuests, 2018)
Part of the pleasure of reading Nabokov is the confrontation with uncomfortable truths, both in a kind of raw form, but also in forms of puzzles, so that the reader is often uncertain as to what kind of questions are being posed, or which links are being made, until careful consideration of the situation at hand. Readers are quite literally seduced by luscious prose, provocative images, and fantastical juxtapositions, a kind of Barthes-like “jouissance” that begins with some level of uncertainty as to what precisely is occurring in any given scene, and follows up with titillating, provocative and sometimes shocking revelations. The puzzle-like quality of the text also leads readers into the processes described by Umberto Eco, in Lector in Fabula, whereby the careful cataloguing of detail, arranging of facts, and inquiries into meanings of particular words or events, gives the reader a task for which she is rewarded with scientific, historical or literary insights that are satisfying, both in themselves, and for the ways that they propel the narrative forward. In this respect, the science of Nabokov’s art underlies the whole project, and this new and magnificent work, Fine Lines: Vladimir Nabokov’s Scientific Art, carefully explains why this is so; in so doing, it brings readers to recognize with awe the breadth and depth of Nabokov’s genius by providing the kinds of detail that is required in order to explain and valorize his scientific accomplishments.